Antecedents and consequences of decisions to venture overseas : the case of Singapore SMEs. - Lei, Fiona Limin. (2008)
This project seeks to explore the antecedents and consequences of decisions to venture overseas – in the case of Singapore SMEs. It is meant to provide a starting point for future research on the effects regionalization and internationalization have on the Small and Medium Enterprises (SMEs), as well as Multi-National Corporations (MNCs) in the long run.